Optimization algorithm and the inverse problems applied to the structural damage identification in steel beams with the use of fem and experimental data - Emidio Sobrinho, Brunno; Gomes, Gilberto; Saleno Yure Rubim Costa Silva, Ramon; Vital da Silva, Welington (Seven Editora, 2023)
Optimization problems are recurrent both in academia and in industry, in addition, the conditions of structural elements throughout their useful life when in use tend to acquire different damages arising from their natural deterioration or even due to the exceptional causes that may lead to these magnitudes. of different damages. In this sense, combining the identification of these damages through optimization processes in the continuous search for more appropriate means and consequently the improvement of the available information that characterizes the problems under study is essential, and constitutes one of the needs of current engineering, because of the evolutionary state structural elements when in use. In this work, it is proposed the adjustment of experimentally tested metallic beam structures, from a static analysis by the Finite Element Method (FEM) using ANSYS© to obtain displacements, as well as the use of inverse problems and an optimization method. From the adjusted models, the damage is simulated (reduction of the stiffness properties of the elements) in the structures, and, then, an optimization and damage identification technique is applied through the Differential Evolution Method (DE). The modeled and experimentally tested metallic beams presented mostly consistent results and the ED technique showed to have good potential for solving damage identification problems using Inverse Problems, managing to converge practically in all cases.DOI: https://doi.org/10.56238/devopinterscie-141